Potential of yellow velvetleaf (Limnocharis flava) as protein source for fish feed - Rusydi, Rachmawati (Universitas Malikussaleh, 2014)
Yellow velvetleaf (Limnocharis flava) is one of aquatic plant which lives by floating on the water. This plant is recognized as vegetable and source of bioactive components. This experiment was purposed to analyze proximate composition of yellow velvetleaf leaves and stems for some parameters such as water content, ash, fat, protein, fibre, and total carotenoid. The methods of this experiment were proximate analysis and total carotenoid analysis of fresh yellow velvetleafs leaves and stems. Result of the experiment showed that fresh yellow velvetleafs leaves contained water content at 91.76% (wet basis), ash at 12.4% (dry basis), fat at 7.95% (dry basis), protein at 22.96% (dry basis), fibre at 11.93% (dry basis), and total carotenoid at 219.01 Î¼g/g. While stems of yellow velvetleaf plant had contents of water at 95.33% (wet basis), ash at 16.38% (dry basis), fat at 5.62% (dry basis), protein at 13.23% (dry basis), fibre at 16.12% (dry basis), and total carotenoid at 92.99 Î¼g/g. Based on its protein and total carotenoids component, yellow velvetleaf leaves had potential as protein source and carotenoid source for fish feed.Tanaman genjer (Limnocharis flava) merupakan salah satu tanaman air yang hidup mengapung di air. Tanaman ini dikenal sebagai sayuran dan sumber komponen bioaktif. Penelitian ini bertujuan untuk menganalisa komposisi proksimat dari daun dan batang genjer untuk beberapa parameter, yaitu kadar air, abu, lemak, protein, serat, dan total karotenoid. Metode penelitian ini adalah analisis proksimat dan analisis total karotenoid dari daun dan batang genjer segar. Hasil penelitian menunjukkan bahwa daun genjer segar mengandung kadar air 91,76% (basis basah), abu 12,4% (basis kering), lemak 7,95% (basis kering), protein 22,96% (basis kering), serat 11,93% (basis kering), dan total karotenoid 219,01 Î¼g/g. Sedangkan batang dari genjer segar mengandung kadar air 95,33% (basis basah), abu 16,38% (basis kering), lemak 5,62% (basis kering), protein 13,23% (basis kering), serat 16,12% (basis kering), dan total karotenoid 92,99 Î¼g/g. Berdasarkan komponen protein dan total karotenoidnya, daun tanaman genjer memiliki potensi sebagai sumber protein dan karotenoid untuk pakan ikan.